Learning experience with a virtual incubator for research on consultation-liaison psychiatry for undergraduate medical students (VIRTUE) - Rincon-Hoyos, Hernan Gilberto; Figueroa-Paz, Roger; Cardozo-Rengifo, Maria Mercedes; Pava-Roldan, Juan Sebastian; Caro-Orozco, Pedro Manuel; Llanos-Leyton, Natalia; Escobar-Florez, Luis Alberto; Prada-Rios, Sergio Ivan (Journal of the Pakistan Medical Association, 2025)
This report discusses the adaptation of a research incubator on Consultation-Liaison Psychiatry to a virtual environment, aimed at promoting research skills through experiential learning. Conducted between March 25, 2020, to June 15, 2021, in Cali, Colombia. The initiative was the result of an alliance between a teaching hospital and a medical university to foster research training competences in undergraduate medical students and psychiatry residents. Based on experiential learning principles, the program used distance education tools to create a virtual research incubator that encouraged active engagement and collaboration. As the initiative progressed, students’ interest, satisfaction and participation gradually increased, highlighting the potential of this approach. Overall, the virtual incubator proved to be a promising strategy to support research training by providing an accessible environment for experiential learning, project follow-ups and interdisciplinary collaboration. Key Words: Experiential learning, Psychiatry, Medical education, Investigative techniques, Distance education.